Upaya Membangun Generasi Islami dan Berprestasi melalui Model Pendidikan Integral (Studi di Al Wildan Isamic School 13 Tambelang) - Azhar, Muhammad; Yani, Ahmad; Nurshabrina, Qonita (YASIN, 2025)
This study investigates the implementation of integral education at Al Wildan Islamic Boarding School 13 Tambelang, focusing on its role in shaping an Islamic generation with high academic and moral achievements. Using a qualitative case study approach, data were collected through interviews, observations, and documentation from school stakeholders, including teachers, students, and parents. The findings reveal that the integral education model successfully integrates Islamic values with modern academic competencies, highlighted by programs such as Tahfizhul Qur’an, leadership training, and extracurricular activities. However, challenges such as balancing academic and religious commitments, student motivation, and parental awareness were identified. The study concludes that the holistic approach of Al Wildan supports the development of students who are both spiritually grounded and academically capable, providing a valuable reference for Islamic educational institutions.